Ornamentals of Rubiaceae Family: current status and potency evaluation of its phytocoenosis for dooryard gardening in Martinique - Jean-Philippe Claude; Nelly Ranguin; Yelji Abati; Philippe Joseph (Ornamental Horticulture)
The Rubiaceae constitute the fourth largest family of flowering plants in the world. It is a cosmopolitan family, present on all continents but a large part of its diversity is located in tropical and subtropical regions. Some species of the family are considered among the most beautiful and popular in the world, but there is little data on the importance and contribution of ornamental Rubiaceae to the thriving global ornamental plant market. The island of Martinique located in the Lesser Antilles archipelago in the Caribbean, hosts part of this diversity of the Rubiaceae family. Despite significant imports of ornamental plants to the French West Indies, these species are almost non-existent in private gardens in Martinique, with the exception of the genera Ixora, Mussaenda, and Gardenia. Using ethnobotanical surveys, we demonstrate that the Rubiaceae family contributes only very weakly to the diversity of ornamental plants in private gardens in the north of the island.